Stimulating the Cochlear Apex Without Longer Electrodes: Preliminary Results With a New Approach. Issue 5 (10th June 2022) - Landsberger, David M.; Stupak, Natalia; Spitzer, Emily R.; Entwisle, Lavin; Mahoney, Laurel; Waltzman, Susan B.; McMenomey, Sean; Friedmann, David R; Svirsky, Mario A.; Shapiro, William; Roland, J. Thomas
Abstract : Objective: To investigate a new surgical and signal processing technique that provides apical stimulation of the cochlea using a cochlear implant without extending the length of the electrode array. Patients: Three adult patients who underwent cochlear implantation using this new technique. Interventions: The patients received a cochlear implant. The surgery differed from the standard approach in that a ground electrode was placed in the cochlear helicotrema via an apical cochleostomy rather than in its typical location underneath the temporalis muscle. Clinical fitting was modified such that low frequencies were represented using the apically placed electrode as a ground. Main Outcome Measures: Pitch scaling and speech recognition. Results: All surgeries were successful with no complications. Pitch scaling demonstrated that use of the apically placed electrode as a ground lowered the perceived pitch of electric stimulation relative to monopolar stimulation. Speech understanding was improved compared with preoperative scores. Conclusions: The new surgical approach and clinical fitting are feasible. A lower pitch is perceived when using the apically placed electrode as a ground relative to stimulation using an extracochlear ground (i.e., monopolar mode), suggesting that stimulation can be provided more apically without the use of a longer electrode array. Further work is required to determine potential improvements in outcomes and optimal signal processing for the new approach.